Associations between genomic aberrations, increased nuchal translucency, and pregnancy outcomes: a comprehensive analysis of 2,272 singleton pregnancies in women under 35 - Huang, Jia; Wu, Dong; He, Jia-Huan; Wang, Jing-Yuan; Li, Xi; Wang, Zheng-Yuan; Wang, Yue; Liu, Hong-Yan (Frontiers in Medicine, 2024)
Objectives: Regarding increased nuchal translucency (NT), the cutoff values used are heterogeneous in clinical practice, this study aims to To assess the efficacy of prenatal detection of for chromosomal abnormalities and pregnancy outcomes in fetuses with varying NT thicknessesincreased nuchal translucency (NT), in order to provide data that supports informed prenatal diagnosis and genetic counseling for such cases. Methods: We included 2,272 pregnant women under 35 with singleton pregnancies who underwent invasive prenatal diagnosis between 2014 and 2022. The cohort comprised 2,010 fetuses with increased NT (≥2.5mm) and 262 fetuses with normal NT but exhibiting a single soft marker. Prenatal diagnoses were supported by chromosomal microarray (CMA) and copy number variation sequencing (CNV-seq) analyses.Results: The detection rates of numerical chromosomal abnormalities were 15.4% (309/2,010) and 17.3% (297/1,717) in the NT ≥2.5 and ≥3.0 groups, respectively. Pathogenic/likely pathogenic CNV incidence increased with NT thickness (χ2=8.60, P<0.05), peaking at 8.7% (22/254) in the NT 4.5-5.4 mm group. Structural defects were found in 18.4% of fetuses with NT values between 2.5 mm and 2.9 mm. Chromosomal abnormality rates in the isolated increased NT groups of 2.5-2.9 mm and 3.0-3.4 mm were 6.7% (16/239) and 10.0% (47/470), respectively, with no statistical significance (χ2=2.14, P>0.05). Combining NT 2.5-2.9 mm with soft markers/non-lethal structural abnormalities increased chromosomal abnormality risk to 19.0%, surpassing the isolated increased N T 3.5-4.4 mm group (13.0%) Fetuses with NT thickness between 2.5 and 2.9mm combined with the presence of soft markers or non-lethal structural abnormalities exhibited a significantly higher chromosomal abnormality risk (19.0%) compared to fetuses with isolated increased NT ranging from 3.5 to 4.4mm (13.0%). Pregnancy termination rates increased with NT thickness (χ2=435.18, P<0.0001), ranging from 12.0% (30/249) in the NT 2.5-2.9 mm group to 87.0% (141/162) in the NT≥6.5 mm group. Conclusion: CMA or CNV-seq exhibited good performance in identifying genomic aberrations in pregnancies with increased NT thickness. NT ranging from 2.5mm to 2.9mm elevated the risk of fetal chromosomal abnormalities, particularly when combined with other soft markers.